Online Relationships and Social Media Interaction in Youth Problem Gambling: A Four-Country Study - Iina Savolainen; Markus Kaakinen; Anu Sirola; Aki Koivula; Heli Hagfors; Izabela Zych; Hye-Jin Paek; Atte Oksanen (MDPI, 2022)
The objective of this study was to examine if belonging to online communities and social media identity bubbles predict youth problem gambling. An online survey was administered to 15–25-year-old participants in the United States (N = 1212), South Korea (N = 1192), Spain (N = 1212), and Finland (N = 1200). The survey measured two dimensions of online behavior: perceived sense of belonging to an online community and involvement in social media identity bubbles. Belonging to an online community was examined with a single item and involvement in social media identity bubbles was measured with the six-item Identity Bubble Reinforcement Scale. The South Oaks Gambling Screen was used to assess problem gambling. Statistical analyses utilized linear regression modeling. According to the analyses, strong sense of belonging to an online community was associated with higher problem gambling, but the association was observed mainly among those young individuals who were also involved in social media identity bubbles. For those youths who did not indicate identity bubble involvement, online relationships appeared to function as those offline. Some differences across the four countries were observed but overall, the results indicate that social media identity bubbles could partly explain the harmful influence that some online relations have on youth behavior.